2021
DOI: 10.1177/15266028211032956
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Suppresses Vasculogenesis Through Regulating Vascular Smooth Muscle Phenotypic Switching

Abstract: Objective: Smooth muscle cell (SMC) phenotypic switching is associated with development of a variety of occlusive vascular diseases. Paeonol has been reported to be involved in suppressing SMC proliferation. However, it is still unknown whether paeonol can regulate SMC phenotypic switching, and which eventually result in suppressing vasculogenesis. Methods: Murine left common carotid artery was injured by completely ligation, and paeonol was administrated by intraperitoneal injection. Hematoxylin and eosin (H&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Based on our previous studies of Paeonol regulated pathological vascular remodeling by monitoring vascular smooth muscle cell phenotypic switching, 26 we hypothesized that Paeonol may contribute to reendothelialization, which is involved in pathological vascular remodeling. We treated HUVEC with Paeonol and performed Real-Time PCR to evaluate vasculogenic signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous studies of Paeonol regulated pathological vascular remodeling by monitoring vascular smooth muscle cell phenotypic switching, 26 we hypothesized that Paeonol may contribute to reendothelialization, which is involved in pathological vascular remodeling. We treated HUVEC with Paeonol and performed Real-Time PCR to evaluate vasculogenic signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Paeonol is a natural ingredient isolated from Paeonia Suffruticosa and Paeonol lactiflora pall. 26 Our previous studies have demonstrated that Paeonol suppresses SMC phenotypic switching associated with neointima formation by inhibiting SMC proliferation and mobility. However, whether inhibition of neointima formation is due to regulating reendothelialization is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For IHC staining, the slides were deparaffinized and antigen retrieval was performed with citric acid treatment at 98°C for 5 to10 min. After antigenic unmasking, the slides were incubated with CD31 (Cell Signaling Technology, 1:200) ( 34 ), HIF-1α (Cell Signaling Technology, 1:200) ( 35 ), and VRGF Receptor 2 (Cell Signaling Technology, 1:200) ( 36 ) overnight at 4°C. This was followed by incubation with biotinylated secondary antibodies at room temperature for 1 h (Vector Laboratories), and incubation in ABC solution (Vector Laboratories) for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Its research indicates that Pae's anti‐myocardial fibrosis effect is related to this pathway (Chen, Zhang, et al, 2022). Pae reduces the possibility of pathological angiogenesis by inhibiting the proliferation and migration of smooth muscle cells (Xu et al, 2022). Similarly, Shi et al (2022) found that Pae inhibited the increase of lipopolysaccharides (LPS) to improve the disorder of intestinal flora and inhibited the proliferation of vascular smooth muscle cells to improve atherosclerosis.…”
Section: The Latest Research Progress Of Paementioning
confidence: 99%